Study of Marriage Verses in Wahbah Zuhaili's Tafsir Al Munir - Wakhdah Faaqih; Sufian Suri; Abdullah Akram; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2024)
This research is motivated by a phenomenon that contrasts with the realization of the sakinah family in community life. The family is the smallest group in society consisting of husband, wife, and children. This is the principle of the formation of society. The majority of people assume that the factor of peace in family life is material, but many rich people do not get peace at home so there are often quarrels and discomfort. Problems that arise in the household can threaten the permanence of marriage and even lead to divorce. This arises due to the unfulfilled expectations of each partner as well as mental, social and spiritual unpreparedness. Furthermore, researchers examined the marriage verses in wahbah zuhayli's tafsir al Munir as a solution in realizing today's sakinah family. The hope is to find relevant and even solutive interpretations to deal with current problems. For the author, it is useful to add insight into mindsets, attitudes, and experiences as an effort to improve the quality of learning, by understanding the character of sakinah, mawaddah, wa rahmah in the family. The formulation of the problem in this study is (1) What is the Qur'anic view of the sakinah family? (2) What is the interpretation of the family verses sakinah, mawaddah, wa rahmah in wahbah zuhayli's tafsir al-Munir?  This research is a literature research that makes tafsir al Munir as the main source of research. This study used a descriptive-analytical approach. The method used is discriptive analysis, which explains interpretation to find out the results of interpretation and differences in the field of interpretation. Another analysis that uses the maudhu'i method is to discuss verses according to the appropriate theme by collecting and studying in depth various aspects related to asbab al-nuzul, mufradat and tafsir of these verses.